Rebuilding Canadian Party Politics. - Cross, William (UBC Press, 2007)
Canadian party politics collapsed in the early 1990s. This book is about that collapse, about the end of a party system, with a unique pattern of party organization and competition, that had governed Canada's national politics for several decades, and about the ongoing struggle to build its successor. Rebuilding Canadian Party Politics discusses the breakdown of the old party system, the emergence of the Reform Party and the Bloc Québécois, and the fate of the Conservative and New Democratic Parties. It focuses on the internal workings of parties in this new era, examining the role of professionals, new technologies, and local activists. To understand the ambiguities of our current party system, the authors attended local and national party meetings, nomination and leadership meetings, and campaign kick-off rallies. They visited local campaign offices to observe the parties' grassroots operations and conducted interviews with senior party officials, pollsters, media and advertising specialists, and leader-tour directors.